Vansakatha Saha Sinhala Bodhi Vansaya - Gunawardhana, N.D. (Vidyalankara, 1997)
When we examine historical data, Vansakatha books become very useful. Deepavansa and Mahavansa are important ancient books. Among the Vansakatha literature, Sinhala Bodhi Vansaya is a significant volume. It explains the history of the Boo tree. Apart from that we can learn about our ancient kings and kingdoms by this book.